PENGEMBANGAN MODEL PENDIDIKAN INTERNET LITERACY PADA ANAK MELALUI PEMBENTUKAN KELOMPOK TEMAN SEBAYA (PEER GROUP) - Mite Setiansah; Wiwik Novianti; Anggun Rahmawati; Lydia Agustina (Institution: Ministry of Communication and Information Technology of Republic of Indonesia, 2021)
The use of the internet among children and adolescents is now unavoidable. The pandemic situation that hit Indonesia in early 2020 also had an impact on increasing ownership and use of internet-based media among children and adolescents. The problem is the limitations of parents in accompanying children to access the internet make parents unable to provide maximum protection for children in facing online risks and dangers. Children also cannot use their parents as a reference when they experience problems using the internet. Friends and siblings then become the child's main point of reference when looking for internet-related information. Starting from this condition, peer groups have great potential to be used as agents of internet literacy education for children. By using descriptive qualitative research methods supported by surveys and FGDs as data collection techniques, this study was conducted to obtain a model for developing literacy education in children through the formation of peer groups. The results showed that middle school age children had a high intensity of online media use, namely on average above 5 hours a day, they also had sufficient technical skills in accessing online media so that they could share knowledge among friends and other family members. It takes the role of schools and the media literacy community to be able to equip children with adequate media literacy education so that they can spread their knowledge to the people around them.